A participação da família no acompanhamento de crianças atendidas em centro especializado de reabilitação - Borges, Natielle Lopes (2021)
This work has as its central axis the discussion on the intervention centered on the family (ICF). The family is an important part of the child development process, as it promotes the child's basic care. When this child presents some alteration in their development, marked by a delay or with a diagnosis of developmental disorder, the care and involvement with this child has another impact on the family. Therefore, the importance of discussing the issue of family involvement in the rehabilitation process of their children under follow-up in a specialized health service. Since the involvement of parents is extremely important, especially in early childhood, when it is understood that early intervention centered on the family is essential. The objective of this study was to understand how the family participates in the monitoring of children at risk of developing or diagnosed with developmental disorders in a health service, as well as the experiences and feelings of families in this process. To this end, a qualitative research was carried out, under the epistemological perspective of social constructivism, in a Specialized Center for Physical and Intellectual Rehabilitation (CER II), located in the interior of the State of Rio Grande do Sul. Fifteen interviews were conducted, of which all family participants of children in early childhood development (0-6 years). As research instruments, semi-structured interviews were used, carried out individually with each participant, these were recorded in audio and later transcribed. The analysis took place through thematic content analysis. It should be noted that all ethical precepts were met in this research, obtaining approval from the Comitê de Ética em Pesquisa da Universidade Federal de Santa Maria. The study results were presented in two scientific articles. The first entitled "The family member's experience with the child who presents atypical development: impacts of the communication of the diagnosis and support network", which aimed to identify the perceptions and feelings of family members regarding the child, the communication of the diagnosis and the support network; the second article, “The perception of families regarding the therapeutic follow-up of children in a Specialized Rehabilitation Center” addressed the perception of families about the assistance and their participation in the rehabilitation process. Both showed how each family prepares the communication of a diagnosis, the daily challenges in the exercise of parenting, as well as the role played by the support network for each family. Finally, we understand the importance of discussions and reflections on this topic, expanding knowledge in the area. In this sense, new studies and the expansion of research on the subject are relevant, since few studies were found that specifically address the participation and involvement of the family when their child is receiving some therapeutic intervention, as well as the attention that is intended for a parental look directed to care.